Exploring the Potential Applications of Blockchain Technology in Accounting Practice: A Systematic Literature Review - Mahdani, Rimal; Risnafitri, Hafizhah; ., Mardiaton (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study aims to examine the potential of blockchain technology in revolutionizing conventional accounting processes and mitigating persistent inefficiencies and problems. This study introduces the potential of blockchain technology to revolutionize conventional accounting processes and address persistent inefficiencies and challenges. By employing a rigorous search methodology, establishing specific criteria for selection, and conducting meticulous data analysis, this paper presents significant discoveries pertaining to the implementation of blockchain technology in the field of accounting. The results suggest an increasing fascination with the potential of blockchain technology to bring about a transformative impact on the accounting sector. The use of blockchain technology in the field of accounting encompasses several areas such as the recording of transactions, automation of accounting operations, and enhancement of auditing procedures. Application of this technology contributes to the improvement of transparency, integrity, and efficiency in financial reporting. However, for widespread adoption to occur, it is imperative to overcome many difficulties like standardisation, interoperability, scalability, legal compliance, and data protection. The study emphasizes the importance of investigating the possibilities of blockchain technology in the field of accounting to address conventional accounting obstacles. The findings of this study may be utilized by researchers to discover potential areas for further research. Additionally, practitioners can acquire valuable insights into the advantages and difficulties associated with implementing these findings.